Oral pioglitazone HCl-loaded solid lipid microparticles: Formulation design and bioactivity studies - Mona Hassan Rafiee, Bazigha K. Abdul Rasool, Mohamed Haider,, Hanan S. Anbar (Journal of Applied Pharmaceutical Science, 2023)
Pioglitazone hydrochloride (PGZ) is a hypoglycemic drug used to treat type 2 diabetes with a short biological half-life and poor oral absorption. The current study was conducted to prepare oral PGZ-loaded lipid microparticles (PGZ-LMPs) for improving PGZ’s solubility and oral bioavailability and maintaining its sustained release. The Design-Expert program was employed to design and analyze various PGZ-LMP formulations. The microparticles were prepared by the solvent injection technique using cetyl alcohol and surfactants. The developed formulations were characterized in vitro for particle size, loading efficiency, and PGZ release. The DDSolver software was employed to investigate the mechanism of the drug release and the appropriate kinetic model for describing PGZ release from LMPs. The optimized formulation was characterized using FT-IR spectroscopy, scanning electron microscopy (SEM), and differential scanning calorimetry (DSC) and was subjected to an in vivo preclinical study to evaluate and confirm its antidiabetic activity. The optimized formula had a mean particle size of 4.73 ± 0.06 nm and a smooth, spherical structure. PGZ-LMPs exhibited excellent homogeneity with a PDI of 0.27 ± 0.06 and showed a high EE% of 71.3% ± 1.293. The FT-IR and DSC analyses confirmed that PGZ was encapsulated in the LMPs and there was no interaction between the excipients and PGZ. PGZ was perceived to be released from the optimized formulation after 8 hours (Q8 = 70.53 ± 0.503). By comparing the Makoid–Banakar equation to other models (R2 = 0.9666) by DDSolver, it proved to be the best model for fitting and describing PGZ release from LMPs (p < 0.05). Finally, the in vivo study on diabetic albino Wistar rats confirmed that the optimized PGZ-LMP formulation resulted in higher therapeutic effectiveness and a prolonged duration of action than the marketed product and control groups.